Evaluating the `logical framework approach' towards learning oriented development evaluation - Gasper, Des (2000)
The logical framework approach has spread enormously, including increasingly to stages of review and evaluation. Yet it has had little systematic evaluation itself. Survey of available materials indicates several recurrent failings, some less easily countered than others. In particular focus on achievement of intended effects by intended routes makes logframes a very limiting tool in evaluation; an assumption of consensual project objectives often becomes problematic in public and inter-organizational projects; and automatic choice of an audit form of accountability as the priority in evaluations can be at the expense of evaluation as learning. - Reproduced
Keywords: Management techniques